PERAN SUPPLY CHAIN MANAGEMENT DALAM PENINGKATAN CUSTOMER VALUE - Christin . (Center for Economic Studies Universitas Katolik Parahyangan, 2003)
Supply Chain Management (SCM) concept is an innovation of scientific development process. It comes to light because of drastic changes that occur in global industrial environment, such as more fierce competition, more demanding consumers and stockholders, shorter product life cycle and also information technology which grows very fast. In applying this concept, many requirements are needed, such as vision and support from top management, government's support and the capability of adopting the technology. Although this concept is not easy to perform, it is beneficial for the company as it can help a company achieve its customer value. Moreover, a company which applies this concept can reduce costs and give a quick response to the customer. Finally, the company that is successful in achieving customer value will be able to survive in the global market for it will create customer loyalty.